2005
DOI: 10.1089/thy.2005.15.931
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Deiodinases in the Central and Peripheral Nervous System

Abstract: Thyroid hormones play a critical role in development and functioning of the nervous system. Deiodinases (type 2 [D2] and type 3 [D3]) contribute to the control of thyroid hormone action in the nervous system by regulating the local concentrations of triiodothyronine (T(3)), the main active thyroid hormone. Most brain T(3) is indeed locally formed by deiodination of thyroxine (T(4)). This reaction is catalyzed by D2 expressed in astrocytes throughout the brain and in tanycytes in the mediobasal hypothalamus. D3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 128 publications
0
25
0
3
Order By: Relevance
“…Furthermore, a different expression of deiodinases in the various brain regions [55], along with the functional heterogeneity of the CNS neurotransmission complex, may be a reflection of the lack of uniformity in the profile of the examined enzyme activities [43,[56][57][58][59]. In addition, in another field of our investigation involving the THs, we concluded that hyperand hypothyroidism seem to be 2 examples of states that cannot be considered as opposing in terms of the response of the (hyper-or hypothyroid) heart to ischemic stress, but are 2 different states that induce distinct forms of adaptation to ischemia (possibly through different mechanisms) [32,60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a different expression of deiodinases in the various brain regions [55], along with the functional heterogeneity of the CNS neurotransmission complex, may be a reflection of the lack of uniformity in the profile of the examined enzyme activities [43,[56][57][58][59]. In addition, in another field of our investigation involving the THs, we concluded that hyperand hypothyroidism seem to be 2 examples of states that cannot be considered as opposing in terms of the response of the (hyper-or hypothyroid) heart to ischemic stress, but are 2 different states that induce distinct forms of adaptation to ischemia (possibly through different mechanisms) [32,60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Although these parameters indicated clearly that marked systemic hyper-and hypothyroidism developed, the T3 level of the cerebral cortex changed only moderately in the treated animals compared to control. In the latter phenomenon the regulatory role of brain deiodinases (among them presumably type D2) could be implicated, since this enzyme converts T4 to the potent form of T3 [16,17]. Finely tuned D2 activity can protect the CNS from significant changes of systemic TH level and results in a steady state TH level in the brain for a prolonged period, even up to 20 days [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that D2 and D3 might be expressed in different testicular cell types localized in specific regions of the organ, as seems to be the case in brain (Courtin et al, 2005). Indeed, very little is known about D2 and D3 specific cellular localization in the developing and mature testis and the level at which they are regulated by thyroid status in these different stages.…”
Section: The Ontogeny Of the Iodothyroninementioning
confidence: 99%